MODELING THE INFLUENCE OF MODERN FACTORS ON EMPLOYMENT TRANSFORMATION IN THE BANKING SECTOR - Domuz, O. (Socio-economic relations in the digital society, 2021)
The study proposed a schematic model of the impact of the financial crisis, the COVID-19 pandemic and the digitalization of the economy on the transformation of employment in the banking sector, which includes two levels of impact of specific markets and specific factors on the transformation of employment in the banking sector. According to the proposed model, the peculiarities of the influence of each factor a teach level are determined, in particular: the first level of influence characterizes the diversity of each factor on certain market types related to the activities of banking institutions, to the analyzed factors. It is determined that the financial capital market, foreign exchange market and labor market react most strongly to the impact of the financial crisis; the impact of the COVID-19 pandemic factor — the health care market, the information market and the labor market; the factor of digitalization of the economy causes changes in the market of innovations, the market of educational services, the information market and the labor market. This points to the close link between the impact of global macroeconomic factors and employment as one of the main elements of the labor market. According to the results of testing the model, changes in the structure of employment in the banking sector under the influence of the financial crisis, the COVID-19 pandemic and the digitalization of the economy are schematically reflected and analyzed. It was found that under the influence of the financial crisis, the employment policy of Ukrainian banks was aimed at the physical reduction of all types and forms of employment, and the structure of non-standard employment remained conservative and unbranched; The impact of the COVID-19 pandemic factor is accompanied by the active introduction and spread of remote employment in all are as of banking, the application of which has shown a number of advantages over traditional forms of employment and expanding the range of other non-standard forms of employment. For the first time in all the practice of economic activity of banks. The impact of the factor of digitalization of the economy on the structure of employment in the banking sector is characterized by the promotion of forms and types of nonstandard employment (freelance and outsourcing). It is determined that the active use of digital technologies in the banking sector has changed the very structure of work, deepening the imbalance between professions.